Occurrence of Oral Ulcerations in Patients undergoing Orthodontic Treatment: A Comparative study - Mainali, Apeksha (Orthodontic Journal of Nepal, 2013)
Introduction: Intra-oral and extra-oral tissues are at risk of damage during orthodontic treatment, most commonly oral ulcerations. Clinicians should assess and monitor every aspect of patient’s treatment procedure to achieve an uneventful and successful final result. Objective: To evaluate occurrence of oral ulcerations in patients undergoing orthodontic treatment. To evaluate the most common type of ulceration and to assess the management of such ulcerations by the orthodontists. Materials & Method: A questionnaire-based study was used among Nepalese and international orthodontists. Data were analyzed statistically using descriptive analysis and Chi-square test, p<0.05 was considered to be significant with a confidence interval of 95%. Result: Most common oral ulceration encountered during orthodontic treatment was traumatic ulceration which was managed by symptomatic measures. There was a statistically significant difference in the method of education to the patients among national and international orthodontists. Conclusion: Careful use of instruments, careful fitting and adjustment of the appliances should be done to avoid oral ulcerations during orthodontic treatment. Topical medicines can be used for management of such ulcers. Nepalese orthodontists should focus on using audio-visual aids for patient education as it has great promise in enhancing patient understanding and in prompting behavioral change.